Co-creation on Redefining Consumer Well-Being Needs Among Youth Through Self-Potential Development Model - Zulkefli, Ahmad Umair; Abdullah, Muhammad Ridhuan Tony Lim; Endut, Mohd Nuri Al-Amin (Frontiers in Psychology, 2022)
A co-creation values consumers’ input as its primary crust in informing businesses on current consumer needs. More importantly, it would be the next shape in future demands of consumers in business sustainability. This paper addressed this context, narrowing its scope in investigating the voices of stakeholders on what would be the essential aspects of the present and future youth qualities in achieving sustainable well-being in the present trend. The findings would be essentially helpful for the youth and the business world to understand the aspects of good youth development, which would shape the next fabric of consumerism. Self-potential development of the youth is vital in achieving excellent life quality and the youth’s well-being in Malaysia. However, the increase in challenges faced by today’s youth is inconsistent with a decline of the group’s well-being. There are various studies and interventions implemented to overcome the youth situation. However, there is still in need for a model that can guide the holistic development of youth self-potential. The purpose of this study is to build a sustainable and comprehensive model of the self-potential development of the youth, which can be integrated with all of the self-potential indicators of the youth via a co-creation process. This study used the Fuzzy Delphi Method (FDM) on the proposed elements in the development model and systematically analyzed them using Interpretive Structural Modeling (ISM) to create the development model. The method capitalized 10 stakeholders from various youth development backgrounds in developing the model. The model consists of 25 sub-indicators (SIs, elements) that are divided into five indicators. The model findings show that one of the most driving indicators is an entrepreneurial mindset among youth, followed by the other indicators of youth self-potential development. The model also shows that the civic-mindedness indicator is the output of youth self-potential that will surface at an end of the development. The model will guide the authorized body on the priority elements that can systematically and strategically improve youth self-potential to meet future challenges with youth aspirations.